2004
DOI: 10.1203/01.pdr.0000145256.19073.e4
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline Reduces Regional Inflammatory and Ventilatory Disturbances in Meconium-Exposed Piglet Lungs

Abstract: Neonatal meconium aspiration frequently produces severe respiratory distress, which is associated with patchy pulmonary neutrophil influx and inflammatory injury. To examine the effects of pentoxifylline (PTX), a potent anti-inflammatory agent, on regional pulmonary inflammation and ventilation after meconium aspiration, we studied 17 anesthetized and ventilated neonatal piglets (age Ͻ2 d) for 12 h. After unilateral intrapulmonary instillation of meconium, PTX treatment was started in nine animals, and eight u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…The samples were initially frozen and later pooled and lyophilized. Before the experiment, meconium was diluted with sterile saline to a concentration of 65 mg/mL 20 . The meconium batch was sterile in culture.…”
Section: Meconium Preparationmentioning
confidence: 99%
“…The samples were initially frozen and later pooled and lyophilized. Before the experiment, meconium was diluted with sterile saline to a concentration of 65 mg/mL 20 . The meconium batch was sterile in culture.…”
Section: Meconium Preparationmentioning
confidence: 99%
“…Studies in rabbits have shown increased levels of CAT, SOD, and GPX during ischemia and reperfusion injury after PTX treatment (17). Studies have also shown that PTX is able to attenuate lung injury related to mechanical ventilation and meconium (18,19). In neonatal HILI models, PTX treatment decreased IL-6 concentration in bronchoalveolar lavage (20), reduced alveolar fibrin deposition, and prolonged survival (21).…”
mentioning
confidence: 99%
“…14 In another animal studies with the same observation time, TNF-a 15 and IL-8 have been detected in bronchoalveolar lavage fluid 16,17 whereas IL-5 and IL-13 were elevated at day 7 in mice. 18 Furthermore, meconium may stimulate chemotaxis, the latter effect claimed to be because of IL-8 present in meconium.…”
Section: Inflammatory Mediators In Masmentioning
confidence: 84%